2017
DOI: 10.18553/jmcp.2017.23.9.980
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Rivaroxaban Compared with Other Oral Anticoagulant Agents Among Patients with Nonvalvular Atrial Fibrillation

Abstract: This research was funded by Janssen Scientific Affairs. Ashton, Crivera, and Schein are employees and stockholders of Janssen Scientific Affairs. Laliberté, Germain, Wynant, and Lefebvre are employees of Analysis Group, a consulting company that received research grants from Janssen Scientific Affairs in connection with this study. McHorney is an employee of Evidera, a consulting company that received research grants from Janssen Scientific Affairs in connection with this study. Peterson received research gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 24 publications
2
38
3
4
Order By: Relevance
“…In our present study, after controlling for differences in patient characteristics (such as lifestyle factors, CHA 2 DS 2- VASc Score, HAS-BLED Score and Frailty Index) between NOAC cohorts, patients starting OAC therapy on rivaroxaban had only a small increased likelihood of discontinuing treatment, while those starting on dabigatran were twice as likely to discontinue, when compared with those starting on apixaban. This is in line with findings from other studies among American and European OAC-naïve NVAF cohorts,13 15 21 but contrasts with those reported by McHorney et al 22 in USA, who found that among 23 309 patients with NVAF starting NOAC therapy, patients treated with rivaroxaban were significantly less likely to discontinue therapy at 1 year, as well as at earlier time points, compared with those starting on apixaban or dabigatran. It should be noted that the higher level of discontinuation seen for dabigatran, both in our study and in others, could be partially explained by its longer market availability.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our present study, after controlling for differences in patient characteristics (such as lifestyle factors, CHA 2 DS 2- VASc Score, HAS-BLED Score and Frailty Index) between NOAC cohorts, patients starting OAC therapy on rivaroxaban had only a small increased likelihood of discontinuing treatment, while those starting on dabigatran were twice as likely to discontinue, when compared with those starting on apixaban. This is in line with findings from other studies among American and European OAC-naïve NVAF cohorts,13 15 21 but contrasts with those reported by McHorney et al 22 in USA, who found that among 23 309 patients with NVAF starting NOAC therapy, patients treated with rivaroxaban were significantly less likely to discontinue therapy at 1 year, as well as at earlier time points, compared with those starting on apixaban or dabigatran. It should be noted that the higher level of discontinuation seen for dabigatran, both in our study and in others, could be partially explained by its longer market availability.…”
Section: Discussionsupporting
confidence: 87%
“…Studies from other European countries have reported either highly comparable,32 notably higher17 or lower15 18 1-year NOAC discontinuation rates based on a 30-day treatment gap,18 60-day treatment gap17 32 or other definition of discontinuation,15 with differences possibly attributable to differences in study size, design and/or composition of the study population (eg, the inclusion of OAC-naïve users only). One-year NOAC discontinuation rates among patient populations with NVAF reported from claims database studies in USA have been substantially higher,21 33 yet are consistent with a trend of higher discontinuation for dabigatran compared with rivaroxaban or apixaban,13 15 17 21 22 32 33 and of rates lowest for apixaban in most,13 15 17 21 33 although not all,22 studies. Most other studies on NOAC discontinuation have reported rates over shorter time periods 34…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…C. McHorney и соавт. проанализировали приверженность к терапии различными ПОАК и варфарином более чем у 36 000 пациентов на основании базы данных IMS [27]. В течение 6 мес доля пациентов, продолжавших прием ПОАК без перерывов (69,2-80,1%) превышала таковую в группе варфарина (64,5%).…”
Section: эффективность и безопасность поак в профилактике сердечно-соunclassified
“…As for medication adherence, the existing results are inconclusive due to the lack of consistent research conditions; one report showed that a DOAC is associated with a higher adherence rate relative to warfarin, while the other found no difference between DOACs and warfarin. 109 , 110 Patients who have been taking warfarin for extended periods of time with satisfactory results tend to elect not to switch to a DOAC. 111 Therefore, there is no reason for physicians to select DOAC therapy for these patients.…”
Section: Introductionmentioning
confidence: 99%